A new phasmid gecko (Squamata: Diplodactylidae: Strophurus) from the Arnhem Plateau: more new diversity in rare vertebrates from northern Australia - Oliver, Paul M.; Parkin, Tom (Zootaxa, 2014)
The Arnhem Plateau is a rugged expanse of sandstone escarpment in the Australian Monsoonal Tropics with a highly endemic biota. Here we describe a new species of small spinifex dwelling Strophurus (phasmid gecko) that also appears to be endemic to this region. Strophurus horneri sp. nov. can be diagnosed from all congeners by aspects of size, coloration and scalation. Even with the description of this new species, however, levels of morphological and genetic diversity within Strophurus from the stone country of the Northern Territory suggest additional divergent lineages are present. A number of recent studies have now provided preliminary evidence of evolutionary diversity within the Arnhem Plateau, but data remains scant and almost nothing is known about how topography and historical processes have shaped the endemic biota of this region.